Outbreaks of peste des petits ruminants in village goat flocks in Nigeria - Opasina, B.A. (Nigerian Veterinary Medical Association, 1985)
Presents a Report on an investigation into the effect of peste des petits ruminats (PPR) outbreaks on the health and productivity of selected village goat populations in southwest Nigeria. Includes data on age & sex distribution of PPR among goats during outbreaks in different villages of Badeku & Eruwa areas. Summurizes an estimation of the economic losses associated with the outbreak.